Intelligent stick with ultrasonic sensor and wifi module / Muhammad Danish Sham - Sham, Muhammad Danish (2024)
Intelligent stick with IoT for disability a set of systems and processes for helping the disability people through its life due to their visual impairment, they have severe mobility and navigational issues. Independent travel is challenging because of the risks posed by environmental obstacles and hazards. Their mobility and safety may be compromised by uneven surfaces, construction zones, and impediments. The main objectives of this project are to design intelligent stick with IoT that can give information about the objects in public places using Arduino Nano as its microcontroller and develop in the mobile app and Internet of Thing (IoT) technology to help mobility for disability person. This report aims to design a Intelligent Stick with IoT for disability that been combined with o microcontroller-based Arduino Nano board and connected to ultrasonic sensor which function to measure any obstacles in front the person from the range of 30cm to 0cm from the stick and give an alert sound using buzzer. Then, the location of the person will be given to the apps by using the GPS module to let the family to know the current location in case of any emergency.